Optimalisasi Branding UMKM Khas Sukabumi Melalui Platform Digital Menuju Pengembangan Ekonomi dan Sosial Berbasis SDGs - Aminullah, Irsyad; Nindya, Regista; Nur Sabrina, Aliya; Putri Rahmah, Marissa; Danial, R. Deni Muhammad (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This research discusses the optimization of branding for Micro, Small, and Medium Enterprises (MSMEs) in Sukabumi City through the use of digital platforms as an economic and social development strategy in line with the Sustainable Development Goals (SDGs), particularly goal 8: decent work and economic growth. With more than 53,000 units, Sukabumi's MSMEs have great potential, but face challenges such as low digital literacy, limited infrastructure, and the absence of an integrated digital platform. Using a qualitative descriptive approach, this study explores MSME digitization strategies and presents a prototype website “UMKM Sukabumi Explorer” as a big data-based solution. Findings show that digital platforms can expand markets, improve competitiveness and strengthen local cultural identity. SWOT analysis identified product diversity, government support, and youth engagement as strengths and opportunities, while technological constraints and perceived digital skills were challenges. The research recommends human resource capacity building, official digital platform development, and cross-sector collaboration to create an inclusive, adaptive, and sustainable digital MSME ecosystem.